Cloud Computing and Firm Growth - DeStefano, Timothy; Kneller, Richard; Timmis, Jonathan (The Review of Economics and Statistics, 2025)
Abstract Cloud computing has shifted how firms access IT away from investment in fixed capital to pay-on-demand services that facilitate remote and simultaneous use. Using firm-level data, we examine the impact of cloud adoption on firm performance and organizational geography with an IV approach that exploits cross-section and time-series variation in fiber broadband speeds as instruments. Cloud leads younger firms to increase revenue, employment, and productivity, whereas incumbent firms experience no scale effects and weaker productivity gains. Incumbents, however, undergo restructuring through establishment deaths and fewer births, while both types of firms experience geographic reorganization shifting farther from the headquarters.